Reduced consumption and use of pods of Vigna species (Leguminosae) by Maruca vitrata (Lepidoptera : Pyralidae) - Oigiangbe, O.N.; Jackai, L.E.N.; Ewete, F.K.; Hughes, Jacqueline d'Arros; Lajide, L. (2002)
The consumption and use of pods of some Vigna (Family: Leguminosae) species by Maruca vitrata F. (Lepidoptera : Pyralidae) were investigated in the laboratory under an ambient temperature of 25 ± 2 °C and 60 ± 20 % relative humidity. The effect of morphological and anatomical characteristics of the pods on their nutritional status was also assessed. Larval mass gain on pods of cowpea cultivars, IT84S 2246 and TVu 13731, was significantly higher than on pods of wild cowpea, TVnu 863, cowpea cultivar, IT91K 180, V. oblongifolia, TVnu 42 and V. vexillata, TVnu 72. The relative consumption rate (RCR) and relative growth rate (RGR) were significantly lower on TVnu 72 pods compared with other plants. Approximate digestibility (AD) was significantly higher on pods of IT91K 180, TVnu 42 and TVnu 863 compared with other plants. There was no difference between plants for efficiency of conversion of ingested food (ECI) and efficiency of conversion of digested food (ECD). Strong, significant positive correlations were found between mass gain and ECD (r = 0.90), RCR and RGR (r = 0.89), as well as RGR and ECI (r = 0.84). The density of glandular trichomes on pods of TVnu 72 was significantly higher than on pods of IT84S-2246 and TVnu 863. The density of nonglandular trichomes was similar among plants, but these trichomes were significantly longer on pods of TVnu 72 than on other Vigna species. There were strong, significant negative correlations between the length of the nonglandular trichomes and RCR,RGR and ECI. Of the 3-4 different layers of cells found in the pod wall of the Vigna species, thickness of the fourth (innermost) layer (endocarp) was significantly negatively correlated with RGR and ECI. Similarly, the thickness of the entire pod wall was significantly, negatively correlated with larval mass gain. Our findings suggest that long, non-glandular trichomes and thick pod walls reduce consumption and use of pods of Vigna species by M. vitrata.